Iowa Birdline update, March 13, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for March 13, 1989. Highlights include the start of migration and the appearance of a second Salty-backed Gull. Epson - sheet feed/flatbed